group-based decision support for flood hazard forecasting: A geospatial technology-based group analytic hierarchy process approach - Lawal, D.U. (Maxwell Science Publications, 2014)
A Geospatial Technology-based Group Analytic Hierarchy Process (GAHP) was carried out to forecast the likely flooded areas based on a total number of five set of criteria/factors believed to be influencing flood generation in the study area. The GAHP is based on two categories of experts (hydrologists and geologists). Priority weights were assigned to each criterion/factor based on Saaty's 9 point scale of preference by the experts and weights were further normalized through the AHP. The ranking given by the two experts were further integrated into GIS environment to come up with the flood forecasting map for the area. These results were further validated using the known Flood Extent Extraction Model developed based on a Minimum Distance Algorithm embedded in ENVI 4.8 software and the Consistency Ratio (CR). Image overlay was carried out in ArcGIS 9.3 software of the two results with the known Flood Extent Extraction Model developed herein. The ranking given by the hydrologists demonstrated a high degree of correlation compared to what is on the ground. Â© Maxwell Scientific Organization, 2014.